2017
DOI: 10.1002/jcb.25832
|View full text |Cite
|
Sign up to set email alerts
|

MCPIP1 Exogenous Overexpression Inhibits Pathways Regulating MYCN Oncoprotein Stability in Neuroblastoma

Abstract: The main physiological function of MCPIP1 (regnase-1) is negative regulation of inflammation. Moreover, roles of regnase-1 in apoptosis and differentiation have also been described, but its involvement in cancer is yet to be fully recognized. Earlier, we showed a lack of expression of MCPIP1 in both primary tumors and several neuroblastoma cell lines. Additionally, we reported that levels of MCPIP1 and the key neuroblastoma oncoprotein-MYCN were inversely correlated in BE(2)-C clones overexpressing the MCPIP1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(50 citation statements)
references
References 51 publications
4
46
0
Order By: Relevance
“…NDRG2 suppresses renal cell carcinoma proliferation and invasion [ 62 , 63 ]. NDRG2 regulation is complex and involves both N-Myc and MCPIP1 [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…NDRG2 suppresses renal cell carcinoma proliferation and invasion [ 62 , 63 ]. NDRG2 regulation is complex and involves both N-Myc and MCPIP1 [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…So far, it has been reported that an antitumour therapy involving proteasome inhibitors led to an upregulation of MCPIP1 . The effects of MCPIP1 expression on breast cancer, clear‐cell renal cell carcinoma (ccRCC), and neuroblastoma (NB) cells were also explored. To date, the effects of MCPIP1 activity on the cell cycle have not been thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Deregulation of miRNA-3613-3p expression in Kelly and BE(2)-C cells with MCPIP1 overexpression, characterized by inhibition of pro-proliferative pathways, suggests its involvement in the regulation of neuroblastoma cell biology. Additionally, it was identified that the overexpression of MCPIP1 protein causes the downregulation of the most potent oncogene in neuroblastoma, MYCN, in two highly tumorigenic cell lines, BE(2)-C and Kelly, as well as inhibition of the Akt/mammalian target of rapamycin signaling pathway (17). Of note, the PANTHER algorithm revealed the potential involvement of miRNA-3613-3p in the regulation of the Akt signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmid vectors used to obtain enforced expression of MCPIP1 protein were as described previously (16). The transfection procedure for Kelly cells was as described in our previous study (17). Overexpression of wild-type or mutated MCPIP1 protein was verified by western blotting.…”
Section: Kelly Cell Transfection With Genetic Constructs Containing Amentioning
confidence: 99%